Autoregressive distributed lag model for determinant of economic growth in Malaysia / Wan Zakiyatussariroh Wan Husin ...[et al.] - Wan Husin, Wan Zakiyatussariroh; Rusfahizan, Ainin Sofiya; Sauji, Nur Syafika Azreen; Tuan Mohammad, Tuan Nur Najwa (Unit Penerbitan UiTM Kelantan, 2021)
In developing countries, economic growth becomes an important element in ensuring the success and prosperity of the country throughout the year including in Malaysia. However, there must be several important factors that affect economic growth in certain countries. Thus, this study sought to investigate the determinant factors that affect the economic growth of Malaysia. The determinant factors that have been used were foreign direct investment (FDI), life expectancy at birth, total natural resources and exports of goods and services. The data used were taken from the World Bank website for years 1970 until 2017 in Malaysia. The Autoregressive Distributed Lag (ARDL) model was used in estimating the relationship and effect of the determinant factors with economic growth. It was found that the trend for FDI and total natural resources tend to decline over time from 1970 to 2017, except for life expectancy at birth and exports of goods and services. Meanwhile, economic growth seems stable over the selected period (2010 until 2017). The findings also revealed that there is a cointegration relationship between economic growth and life expectancy at birth, FDI, total natural resources and exports. Hence, it is hoped that findings of this study may add to the literature in developing a good macroeconomic environment in the country.